Root fracture resistance test of cast post using seat and non-seat preparation design in central maxillary incisor - Pramanik, Rifki Kania; Subrata, Gantini; Kurnikasari, Erna (Padjadjaran Journal of Dentistry, 2009)
Post-placement is one of the treatment plans supporting the success of a restoration. The design of root canal preparation is a factor in the success of post-use. The purpose of this study was to investigate the root fracture resistance of the root canal preparation for cast post with a seat and non-seat preparation. The study was a laboratory experimental study using 20 upper central incisors that met the criteria in the study. Ten incisors were prepared using seat design while the other ten were prepared using non-seat design. Then tested the compressive test by Universal Testing Machine with test speed 0,5 mm/min. The results of the fracture strength were analyzed using t student statistical test. The analysis showed a significant difference between the non-seat group and the seat group (Î±=0.05). The average force in the non-seat group was 852.27 N with a standard deviation of 112.6 N while the seat group showed a value of 495.78 N and 82.90 N, respectively. It was concluded therefore that the root fracture resistance in the non-seat root canal preparation design was higher than the seat preparation design.